(untitled) - Peck, Amelia (New York, 2007)
This book gives the reader an even greater understanding and admiration of quilting as Americana. Special features include an illustrated Highlights section and all-new technical appendix by Elena Phipps, the Museum's Senior Conservator in the Department of Textile Conservation. Museum curator and respected authority Amelia Peck contributes new scholarship and an informative and entertaining
Keywords: Textile crafts,Dệt thủ công; Vietnam,Việt Nam